2017
DOI: 10.1248/bpb.b17-00091
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of the Activators of the Nuclear Factor Erythroid 2-Related Factor 2–Antioxidant Response Element Pathway in Brain Disorders

Abstract: Oxidative stress is recognized as an important mediator of brain disorders. Nevertheless, there are few antioxidants approved for brain diseases. There are two types of mechanisms as antioxidant systems in vivo, antioxidants and antioxidant enzymes. Antioxidants are consumed by the reaction with reactive oxygen species. Thus, it is important to maintain high concentrations at the requisite site. On the other hand, antioxidant capacity is maintained for around a half-day to one day once antioxidant enzymes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One of the most studied antioxidant factors in the brain that directly regulates GSTs is the nuclear factor erythroid 2 (NFE2)-related factor 2 (Nrf2). Multiple studies have found that increasing Nrf2 activity can protect cells in the brain from oxidative stress [26]. Interestingly, there are multiple SNPs that were found in the promoter of Nrf2, and some of these polymorphisms led to reduced antioxidant response [27].…”
Section: Genetic Contributors To Brain Sensitivitymentioning
confidence: 99%
“…One of the most studied antioxidant factors in the brain that directly regulates GSTs is the nuclear factor erythroid 2 (NFE2)-related factor 2 (Nrf2). Multiple studies have found that increasing Nrf2 activity can protect cells in the brain from oxidative stress [26]. Interestingly, there are multiple SNPs that were found in the promoter of Nrf2, and some of these polymorphisms led to reduced antioxidant response [27].…”
Section: Genetic Contributors To Brain Sensitivitymentioning
confidence: 99%
“…Nrf2 protects neurons by transcriptionally upregulating antioxidant enzyme genes that suppress oxidative stress. Several previous studies have demonstrated that oxidative stress, neuroinflammation, and neuronal injury can be prevented by increasing the activation of the Nrf2-related pathway [ 23 , 24 ]. The purpose of this study was to evaluate the effects of NXP032 on oxidative stress and cognitive dysfunction induced by aging by activating the Nrf2-ARE pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a major cause of death and disability and ischemic stroke is the most widely recognized type of stroke. [1][2][3] Reperfusion of the blocked vessel is the standard treatment for patients diagnosed with ischemic stroke, but it may cause a cascade of secondary injuries. 4) The early inflammatory response to brain injury has great importance in the pathogenesis of ischemia/reperfusion (I/R) injury and this has produced enthusiasm for developing anti-inflammatory cures to combat I/R-caused damage.…”
Section: Introductionmentioning
confidence: 99%